STRATEGIC DIRECTIONS FOR DEVELOPMENT OF THE BUDGET SYSTEM AND ITS MODERN ECONOMIC IMPORTANCE IN UZBEKISTAN (Academicia Globe: Inderscience Research, 2021)
In this article, the Budget Code, which provides the ongoing and high-quality development of the Republic of Uzbekistan on the budgetary, and the tax code, as well as the tax code, and the imposition of the levels of inflation, and the imposition of inflation to secondary budget plans, as well as the tax code, it is also reflected in the principles of the budget openness.